2019
DOI: 10.1002/ps.5659
|View full text |Cite
|
Sign up to set email alerts
|

Natal origin of the invasive biosecurity pest, brown marmorated stink bug (Halyomorpha halys: Penatomidae), determined by dual‐element stable isotope‐ratio mass spectrometry

Abstract: BACKGROUND Post‐border detection of a single brown marmorated stink bug (BMSB) in New Zealand warranted a biosecurity response, the nature of which would be influenced by its status as part of an established population or as a new arrival. Stable isotope analysis has the potential to determine natal origins, but is difficult to achieve for samples as small as a single insect. Here an analytical modification to measure small samples was successfully trialled as a means to supply evidence as to the local or exot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…One of the highest risk pests for Aotearoa is the exotic brown marmorated stink bug ( Halymorpha halys ) because it feeds on over 300 species of plants and infestation can ruin entire crops [ 7 ]. Recent attempts to define the origins of this invasive stink bug used δ 2 H and δ 18 O isotopes from their wings to determine whether a bug detected post-border represented a recently introduced foreign bug or an established population [ 2 ]. Holder et al [ 2 ] concluded that the distinct δ 2 H and δ 18 O isotope signature of their wings suggested a cooler climate origin, supporting evidence that the specimen was not from a locally breeding, southern hemisphere summer population.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the highest risk pests for Aotearoa is the exotic brown marmorated stink bug ( Halymorpha halys ) because it feeds on over 300 species of plants and infestation can ruin entire crops [ 7 ]. Recent attempts to define the origins of this invasive stink bug used δ 2 H and δ 18 O isotopes from their wings to determine whether a bug detected post-border represented a recently introduced foreign bug or an established population [ 2 ]. Holder et al [ 2 ] concluded that the distinct δ 2 H and δ 18 O isotope signature of their wings suggested a cooler climate origin, supporting evidence that the specimen was not from a locally breeding, southern hemisphere summer population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent attempts to define the origins of this invasive stink bug used δ 2 H and δ 18 O isotopes from their wings to determine whether a bug detected post-border represented a recently introduced foreign bug or an established population [ 2 ]. Holder et al [ 2 ] concluded that the distinct δ 2 H and δ 18 O isotope signature of their wings suggested a cooler climate origin, supporting evidence that the specimen was not from a locally breeding, southern hemisphere summer population. Currently, there are no rapid response tools to assess the provenance of these pests when they are introduced which limits the ability to develop effective measures to prevent their arrival in Aotearoa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations